The Impact of Environmental Awareness, Market Information Access, and Organizational Involvement on Students' Career Choices in the Agricultural Sector - D. Yadi Heryadi; Sonny Santosa; Amruddin Amruddin; Suherlan Suherlan; Mulyadi Mulyadi; Moses Odhiambo Okombo (Bulletin of Social Studies and Community Development, 2026)
This study examines the influence of environmental awareness, market information access, and organizational involvement on students’ career choices in the agricultural sector, with the perceived economic value of agriculture serving as a mediating variable. The study addresses the growing concern over declining youth interest in agricultural careers despite the sector’s strategic role in food security and sustainable economic development. A quantitative research design was employed, using a survey of 100 undergraduate students from universities in the Karawang region, Indonesia, selected through purposive sampling based on their educational background and familiarity with agricultural issues. Primary data were collected using a structured questionnaire consisting of validated indicators measured on a five-point Likert scale to assess environmental awareness, market information access, organizational involvement, perceived economic value, and career choice intentions. Data were analyzed using Structural Equation Modeling–Partial Least Squares (SEM-PLS) to evaluate both the measurement and structural models. The findings indicate that environmental awareness and market information access have significant positive effects on students’ career choices in the agricultural sector. In contrast, organizational involvement does not exert a significant influence. Furthermore, perceived economic value has a significant direct effect on career choice and partially mediates the relationship between market information access and career choice. However, it does not mediate the relationships between environmental awareness or organizational involvement and career choice. These findings suggest that improving access to reliable agricultural market information and strengthening students’ understanding of the economic potential of modern agriculture can enhance their interest in pursuing agricultural careers. The study provides practical implications for universities, policymakers, and agricultural stakeholders to develop sustainability-oriented educational programs, digital agricultural information platforms, and career promotion initiatives that encourage greater youth participation in the agricultural sector. Keywords: Environmental awareness, Market information access, Organizational involvement, Students' career choices, Perception of economic value.